The Effect of Native-English-Speaking Teachers on EFL Learners’ Attitudes and Motivation in Learning English as an International Language - Ismar, Randila Tiayu; Refanja Rahmatillah (Indonesian Journal of Teaching and Teacher Education, 2024)
The increasing demand for Native-English-Speaking Teachers (NESTs) in English as a Foreign Language (EFL) contexts has raised debates on their effectiveness in influencing learners' attitudes and motivation compared to Non-Native English-Speaking Teachers (NNESTs). This study aims to analyze the impact of NESTs on EFL learners’ attitudes and motivation in learning English as an International Language (EIL) by employing a literature review method. Academic articles from 2010 to 2024 were examined to synthesize evidence on the topic. The findings reveal that while NESTs are often regarded as proficient language models, they face challenges related to understanding students’ linguistic problems, teaching methodologies, and cultural contexts. Conversely, NNESTs demonstrate better empathy towards learners' difficulties and familiarity with local educational systems, fostering positive attitudes and higher motivation among students. Furthermore, misconceptions about the superiority of NESTs over NNESTs are debunked, showing that teacher effectiveness is not solely determined by their native status. The study concludes that the presence of NESTs in EFL contexts does not necessarily enhance students’ attitudes and motivation, emphasizing the need for pedagogical training and cultural sensitivity in teaching English as an international language.